ETIKA PENDIDIK DAN PESERTA DIDIK MENURUT PERSPEKKTIF IMAM AL-GHAZALI - Lala Dyah Chandra; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The decline in ethics has occurred all around us, whether from school institutions or the community has received a lot of public attentio. Many cases occur and we can know that one of them is an event that occurs between educators and students, the incident even to the point of sacrificing human souls. Therefore,This study explains the ethics of educators and students based on the perspective of Imam al-Ghazali. By using several literature sources, produces literature results in the amount of 8 articles, 1 thesis, and 6 theses. This study uses the SLR method (systematic literature review).Literature sources were obtained from the Google Scholar database and the Garuda Portal in 2018-2022. The results of this study produce several ethics of educators and students based on the perspective of Imam al-Ghazali,which is useful as a guide for educators and students as well as its implementation in society.